Bengali language situation in the judicial system in Bangladesh - Ferdouci, Nahid (Dhaka University Journal of Linguistics, 2010)
Bengali language has been declared as the state language of the Republic in Article 3 of the Constitution of Bangladesh. Bengali is our mother tongue and we have achieved this at the cost of much blood. Moreover Bangla Bhasha Procholon Ain (Bengali Language Implementation Act) was made in 1987 for ensuring compulsory use of Bengali in courts and offices of Bangladesh. In spite of these provisions, English is still used in the judicial system (Higher Courts) in Bangladesh. Often delivering of judgments in English creates various problems for poor and illiterate person. People in our country speak in Bengali. Language of courts should follow the language of the common people. An attempt has been made in this article to assess the status and the enforceability of Bengali language with historical background, limitations of bringing into practice and some necessary measures for effective use of Bengali language in the courts. Key words: Bengali language, judgments in English, impact on the people DOI: 10.3329/dujl.v2i3.4143 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 53-68